The Peran Tokoh Agama dalam Meningkatkan Pembinaan Akhlak Remaja di Kampung Pamuruyan - Agung, Ujang Pupuh; Dedi Supriadi; Hambari (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
The role of religious figures is a person who carries out da'wah both orally and in writing or deeds either individually, in groups or in the form of certain organizations or institutions. This study aims to find out how the role of religious leaders in improving youth moral development in Pamuruyan Village, Balekambang Village, Jonggol District, Bogor Regency, to find out the Solutions of Religious Leaders in improving youth moral development in Pamuruyan Village, Balekambang Village, Jonggol District, Bogor Regency, to find out how the morals of adolescents after coaching by religious leaders. This study used qualitative methods used to examine the condition of natural objects, so researchers collected data from informants religious figures. The results of observations in Pamuruyan village, Balekambang village, Jonggol district, Bogor regency, the role of religious leaders in dealing with several factors in improving adolescent moral development, including where the first factor is due to lack of attention from the family, second, environmental factors and lack of awareness of themselves in carrying out religious activities, for example praying in congregation at the mosque and following routine recitations held by religious leaders and carrying out activities Socializing, for example, working together, among others, to improve moral development aims to call and invite teenagers to participate in carrying out worship. Religious leaders can increase more activities involving teenagers, so that adolescents will be more accustomed to positive activities, which more or less reduce the negative influence on the morals of adolescents in Pamuruyan village.